2009
DOI: 10.1063/1.3075830
|View full text |Cite|
|
Sign up to set email alerts
|

On polynomial invariants of several qubits

Abstract: It is a recent observation that entanglement classification for qubits is closely related to local $SL(2,\CC)$-invariants including the invariance under qubit permutations, which has been termed $SL^*$ invariance. In order to single out the $SL^*$ invariants, we analyze the $SL(2,\CC)$-invariants of four resp. five qubits and decompose them into irreducible modules for the symmetric group $S_4$ resp. $S_5$ of qubit permutations. A classifying set of measures of genuine multipartite entanglement is given by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 24 publications
2
65
0
Order By: Relevance
“…With this definition H has a (physically irrelevant) prefactor of 2 compared to the definitions in [198] and [199]. We note that this quantity, in a strict sense, cannot be a measure of genuine entanglement as it yields 1 on a tensor product of two two-qubit Bell states [200].…”
Section: Four-qubit Invariantsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this definition H has a (physically irrelevant) prefactor of 2 compared to the definitions in [198] and [199]. We note that this quantity, in a strict sense, cannot be a measure of genuine entanglement as it yields 1 on a tensor product of two two-qubit Bell states [200].…”
Section: Four-qubit Invariantsmentioning
confidence: 99%
“…There are the degree-8 filter F (4) 2 , and the degree-12 filter F (4) 3 [58,202,199] whose precise definitions are also given in section 6.4.4. The peculiarity of the filters F…”
Section: Four-qubit Invariantsmentioning
confidence: 99%
“…As a Platonic state, it is an optimal state for reference frame alignment [106], and in terms of symmetric informationally complete positive-operator-valued measures (SIC POVM) [182,183] it was found that the tetrahedron state is the unique state that can be generated in the setting of a two-dimensional Hilbert space [110,183]. In Section 5.7 it will be outlined that -along with the four qubit cluster state and GHZ state -the tetrahedron state is one of the three maximally entangled four qubit states under a monotone that requires all k-tangles with k < 4 to vanish [58,62].…”
Section: Four Qubitsmentioning
confidence: 99%
“…For 4 qubits there exist three inequivalent SLOCC invariants 8 , and a corresponding "basis" of three inequivalent maximally 4-tangled states with neither 3-tangle nor concurrence has been determined [58,62]. These states are the GHZ state (|1111〉 + |1100〉 + |0010〉 + |0001〉) .…”
Section: Global Entanglement Measuresmentioning
confidence: 99%
See 1 more Smart Citation